Wicked Māra, a true opponent of Nirvāṇa: A Critique - Panda, N.C. (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย; Vol 10 No 2 (2018): วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2020)
In the Buddhist Mythology Māra possesses a very prominent figure. It always follows Buddha’s religious and true austerity life. Due to Māra’s bad intension for providing different materialistic happiness to the Buddha, his austerity life became prejudiced. But the great Buddha’s sādhanā was free from Māra’s bad influence and inert effort. The Māra was a dominant figure in Gautama Buddha’s period as he has an assembly. Māra, the greatest opponent of enlightenment, is depicted in different Pāli texts in the appearance of a thoroughly personified supernatural and bitterest enemy of the Buddha, rather than in the form of an abstract (nirākāra) idea of metaphysical character; the idea of the evil and ignorance in opposition to the good and insight. The fetter of Māra was really an obstacle for Buddha in the way of his religious journey. This paper will discuss in detail regarding Mara’s ill activities to subdue Lord Buddha in several ways, but finally failed to get success over Lord Buddha. However, the paper will also discuss the victory of Buddha over his enemy Māra in a most.